Blood Monocytes and Their Subsets: Established Features and Open Questions - Ziegler-Heitbrock, Loems (Frontiers in Immunology, 2015)
In contrast to the past reliance on morphology the identification and enumeration of blood monocytes is nowadays done with monoclonal antibodies and flow cytometry and this allows for subdivision into classical, intermediate and non-classical monocytes. Using specific cell surface markers dendritic cells in blood can be segregated from these monocytes. While in the past changes in monocyte numbers as determined in standard hematology counters has not had any relevant clinical impact, the subset analysis now has uncovered informative changes that may be used in management of disease.